Global Strong Le Chatelier-Samuelson Principle - Fujimoto, Takao (Econometrica, 1980)
[In this paper the Le Chatelier principle for a Leontief model due to Samuelson and Morishima is extended to a more general system of nonlinear equations. The global strong version of the principle as well as the weak one is presented without using any determinant theory or calculus. The strong version is concerned with comparative statics when some constraints are relaxed together with changes in parameters. It is also shown that our results are applicable to the system of excess demand functions which satisfy the gross substitute condition.]